Futures markets : an overview of the AEI studies - Johnson, Philip McBride; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1986)
This volume is based on a series of AEI studies of futures markets, published in two volumes, Futures markets--their economic role, and Futures markets--regulatory issues, edited by Anne E. Peck"--P. [4] of cover.It provides a careful analysis of future markets, its instruments and industrial practices.
Includes bibliographical references in "Notes".
kjo 25/01/2019
Loans
Keywords: Commodity exchanges; Futures market